Resource Based View: A Promising New Theory for Healthcare Organizations; Comment on: "Resource Based View of the Firm as a Theoretical Lens on the Organisational Consequences of Quality Improvement" - Ewan Ferlie (Kerman University of Medical Sciences, 2014)
This commentary reviews a recent piece by Burton and Rycroft-Malone on the use of Resource Based View (RBV) in healthcare organizations. It first outlines the core content of their piece. It then discusses their attempts to extend RBV to the analysis of large scale quality improvement efforts in healthcare. Some critique is elaborated. The broader question of why RBV seems to be migrating into healthcare management research is considered. They conclude RBV is a promising new theory for healthcare organizations.